2020
DOI: 10.3390/ijgi9070454
|View full text |Cite
|
Sign up to set email alerts
|

Population Trends and Urbanization: Simulating Density Effects Using a Local Regression Approach

Abstract: Density-dependent population growth regulates long-term urban expansion and shapes distinctive socioeconomic trends. Despite a marked heterogeneity in the spatial distribution of the resident population, Mediterranean European countries are considered more homogeneous than countries in other European regions as far as settlement structure and processes of metropolitan growth are concerned. However, rising socioeconomic inequalities among Southern European regions reflect latent demographic and territorial tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…Polinesi, who used Greek cities as an example to establish a partial regression model and found that population growth is internally affected by cities with different levels of development 19 . The difference from previous research is that we deduce the change law of spatial population distribution in the urban agglomeration, thus, we can argue the determining factors of this law.…”
Section: The Urban Population Of Different Development Levels In Urban Agglomerations Has Different Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polinesi, who used Greek cities as an example to establish a partial regression model and found that population growth is internally affected by cities with different levels of development 19 . The difference from previous research is that we deduce the change law of spatial population distribution in the urban agglomeration, thus, we can argue the determining factors of this law.…”
Section: The Urban Population Of Different Development Levels In Urban Agglomerations Has Different Trendsmentioning
confidence: 99%
“…At the rst stage, the scale of the urban population increased signi cantly. At the second stage, the urban population tends to saturate and grow slowly 19 . Taking Athens of Greece as an example, from 1950 to 2000, it had been a linear growth, and the growth rate was relatively high, from 2001 to 2020, the development of the permanent population tends to be slow 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The cluster characteristics are emphasized with the use of Moran's I and LISA to prescreen the spatial autocorrelation effects [32,36,39,43,45,47,48]. LISA is modified from Moran's I to indicate the cluster for each location [49], and was included to provide the local spatial autocorrelation.…”
Section: Spatial Autocorrelation and Heterogeneitymentioning
confidence: 99%
“…Figures of a consolidated city-county (the unified administrative body of Taichung city is used as the case study) were extracted to explore dramatic changes in socio-economic variables. To diminish the bias of long-term changes and variance in non-linear regression analysis, local indicators of spatial association (LISA) was applied to identify local clusters and to screen a better bandwidth, which is needed in GWR analysis [32,38,44,45]. Multicollinearity was removed with OLS.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research on urban population density and urban growth in European and American countries continues to make progress, accompanied by the improvement of methods. For example, Polinesi et al try to reflect the relationship between population trends and urbanization in Greece by simulating density effects using a local regression approach [14]. Mariani et al illustrates a simplified procedure identifying population sub-centers over 50 years in three Southern European cities (Barcelona, Rome, Athens) by identifying metropolitan subcenters from diachronic density-distance curves [15].…”
Section: Introductionmentioning
confidence: 99%